Application of Geographical Infomation System (GIS) to Study Diversity of Habitat Structure of Spider in Agricultural Landscape in Cianjur Watershed - I Wayan Suana (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2009)
Spiders are dominant predators and have an important role not only in ricefield ecosystem, but also in agroecosystem in general. The complexity of landscape structure is expected to have an important role to the availability of spiders in ecosystem. Aim of this research were mapped agricultural landscape in Cianjur Watershed and to study the influence of landscape structure complexity to the diversity of spider in the landscape. Research was conducted at agricultural landscape in Cianjur Watershed, i.e: upper part (Nyalindung Village), middle part (Gasol Village) and lower part (Selajambe Village), from January to September 2003. Agricultural landscape in Cianjur Watershed were mapped by using Global Positioning System (GPS), Arc View GIS 3.2. computer program, and Digital Indonesian Land Use and Topographical Map from Bakosurtanal. These instruments were used to make a new map which consist of information of land use system. Spider in agricultural landscape were sampled by using two trapping techniques, i.e: pitfall trap and sweep net. The results showed that landscape structure at upper part of Cianjur Watershed is more complex than that of at midlle and lower part. The diversity of spider at upper part of Cianjur Watershed was also higher than that of middle and lower part. Thus, the complexity of landscape structure significantly influence to the diversity of spiders in the agricultural landscape.